1990
DOI: 10.1108/eum0000000002586
|View full text |Cite
|
Sign up to set email alerts
|

Framing and Sales Promotions: The Characteristics of a ″Good Deal″

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 2 publications
3
90
0
3
Order By: Relevance
“…Past research on framing of sales promotion has found that non-monetary promotions are more likely to be framed as gains, whereas monetary promotions are framed as reduced losses Campbell and Diamond, 1990;Diamond and Campbell, 1989;Diamond and Johnson, 1990;and Diamond and Sanyal, 1990). For example, Campbell and Diamond (1989) found that consumers regarded non-monetary promotions, such as free goods or extra amounts of the product, as "extra gains," while they regarded monetary promotions, such as discounts, as "reduced losses (losing less than usual)."…”
Section: Effect Of Coupon Benefit On Redemption Ratementioning
confidence: 99%
“…Past research on framing of sales promotion has found that non-monetary promotions are more likely to be framed as gains, whereas monetary promotions are framed as reduced losses Campbell and Diamond, 1990;Diamond and Campbell, 1989;Diamond and Johnson, 1990;and Diamond and Sanyal, 1990). For example, Campbell and Diamond (1989) found that consumers regarded non-monetary promotions, such as free goods or extra amounts of the product, as "extra gains," while they regarded monetary promotions, such as discounts, as "reduced losses (losing less than usual)."…”
Section: Effect Of Coupon Benefit On Redemption Ratementioning
confidence: 99%
“…However, many researchers mention that a range of promotions involving monetary and non-monetary methods have been used and further added that there is a big difference between the two strategies (Campbell & Diamond, 1990, Tellis 1998. Free rewards are given to the consumer immediately on purchase of products and are transactional in character.…”
Section: Types Of Sales Promotionmentioning
confidence: 99%
“…On the other hand, non-price promotions such as free gifts, free samples, sweepstakes and contests in communication strategies are becoming very popular among retailers [Palazón and Delgado-Ballester 2009]. Non-price promotions do not influence individuals' internal reference prices and consequently are less likely to create a negative influence on the consumer's perceptions of brands [Campbell and Diamond 1990]. Similarly, nonprice promotions help communicating distinctive brand attributes and contribute to improve brand equity [Chu and Keh 2006].…”
Section: Antecedents Of Sbbementioning
confidence: 99%